Effect of augmented nutrient composition and fertigation system on biomass yield and cannabinoid content of medicinal cannabis (Cannabis sativa L.) cultivation - Velechovský, Jiří; Malík, Matěj; Šenkyřík, Josef Baltazar; Tlustoš, Pavel (Frontiers in Plant Science, 2024)
Growing evidence underscores the role of nutrients and fertigation systems in soilless production, influencing medicinal cannabis biomass and secondary metabolite content. This study delves into the impact of enhanced nutrient regimes on the 'ionome' and its ramifications for biomass and cannabinoid production in medicinal cannabis, comparing two distinct fertigation systems: recirculation and drainto-waste. Notably, we assess the optimal harvest time for maximizing profitability. In comparing the experimental variant with elevated levels of phosphorus (P), potassium (K), and iron (Fe) in the nutrient solution to the control variant, we observe distinct patterns in element composition across stems, leaves, and flowers, with significant differences between fertigation systems. Total nitrogen content was determined through the Kjeldahl method. Flame atomic absorption spectrometry (FAAS) and inductively coupled plasma optical emission spectrometry (ICP-OES) were employed for elemental analysis. Cannabinoid identification and quantification used high-performance liquid chromatography with a diode-array detector (HPLC/DAD). Followed statistical analyses included ANOVA and Tukey's HSD test. Although the augmented nutrient regimen does not substantially increase plant biomass, interesting differences emerge between the two fertigation systems. The recirculation fertigation system proves more profitable during the recommended harvest period. Nonetheless, the altered nutrient regime does not yield statistically significant differences in final inflorescence harvest mass or cannabinoid concentrations in medicinal cannabis. The choice of fertigation system influences the quantity and quality of harvested inflorescence. To optimize the balance between the dry biomass yield of flowers and cannabinoid concentration, primarily total THC yield (sum of tetrahydrocannabinolic acid, Δ 9 -tetrahydrocannabinol, and Δ 8 -tetrahydrocannabinol), we propose the 11th week of cultivation as the suitable harvest time for the recirculation system. Importantly, the recirculation system consistently outperformed the drain-to-waste system, especially after the ninth week, resulting in significantly higher total THC yields. Enriched nutrition, when compared with control, increased THC